Enhancing cave seismic monitoring with distributed acoustic sensing and template matching - Czarny, R.; Birch, D.J.; Enslin, R.; Goldswain, G.; Pilkington, J.; Sanker Pararath, G. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Distributed acoustic sensing (DAS) is increasingly deployed in underground mining to support seismic monitoring due to its dense spatial coverage and flexible installation. Despite these advantages, the use of DAS for cave-front tracking has not yet been fully explored. This study presents the application of a well-known seismological template-matching method to DAS data to improve the detection of weak, repeating seismic events associated with cave establishment firings. The approach relies on waveform templates selected from previously identified events and applies them to continuous DAS records to search for similar signals, including weak events that may be missed by standard detection procedures used in conventional underground geophone arrays. By increasing the number of detected events, the approach enhances the effective spatial resolution of microseismic observations in the cave environment. The workflow is demonstrated using DAS data acquired during active cave development at an underground mining operation. The results show that the method increases the number of detected events and better defines the seismicity pattern associated with cave establishment firing. The resulting catalogue provides a clearer view of the rock mass response to mining and supports more reliable cave-tracking interpretation. Overall, the results demonstrate that template matching can substantially extend the practical capability of DAS-based microseismic monitoring for cave-tracking applications. The approach integrates with existing monitoring workflows and adds value without requiring changes to acquisition geometry or hardware.